A longitudinal study of the bidirectional causal relationships between online political participation and offline collective action. (August 2021) - Chayinska, Maria; Miranda, Daniel; González, Roberto
Abstract: The longitudinal causal relationships between individuals' online and offline forms of civic participation requires further understanding. We provide a robust test of four competing theoretical perspectives to establish the direction of causality between online political participation and offline collective action as well as the persistence of their longitudinal effects. Two longitudinal panel studies were conducted in the socio-political context of Chile. Study 1 involved university students (a 2-year, 5-wave longitudinal study, N wave 1 = 1221, N wave 2 = 954, N wave 3 = 943, N wave 4 = 905, and N wave 5 = 786) and Study 2 used a nationally representative sample of adults (a 3-year, 3-wave longitudinal study, N wave 1 = 2927, N wave 2 = 2473 and N wave 3 = 2229). Results from both studies supported the spillover perspective compellingly showing that offline participation fostered subsequent online collective action over time, whereas the reverse causal path from online political participation and offline collective action was consistently non-significant. In Study 2, previous offline collective action predicted increased online participation after controlling for the effects of age, gender, and educational level. The need for further fine-grained longitudinal research on the causal relations between offline and online collective action is discussed. Highlights: The bidirectional causal longitudinal link between online political participation and offline collective action was explored. Four theoretical causal hypotheses were systematically analyzed using longitudinal cross-lagged modelling Panel data collected from Chilean university students and the nationally representative sample of Chilean adults were used. Results show that pursued past offline collective action can mobilize further durable online political participation. The reverse path from online political participation to offline collective action was consistently non-significant.